Strengthening ecosystem sustainability and climate resilience through integrative nature-based solutions in Bontioli Natural Reserve, West African Drylands - Kiribou, Issaka Abdou Razakou; Dimobe, Kangbéni; Workeneh, Sintayehu Dejene (Multidisciplinary Digital Publishing Institute, 2025)
Natural reserves in the West African drylands play a critical role in sustaining livelihoods and preserving ecological integrity. However, these ecosystems face growing threats from climate variability and anthropogenic pressure. This study assesses the potential of Nature-based Solutions (NbSs) to enhance climate resilience and mitigate human-induced degradation in Bontioli Natural Reserve (BNR), one of the region’s key biodiversity hotspots. We employed an integrated approach combining ecological assessments, climate and anthropogenic pressures analysis, and participatory governance framework. Generalized additive modeling (GAM) is applied to assess the long-term vegetation response to climate stressors. A conceptual framework that integrates climate resilience with socio-ecological systems is developed for synergies conservation. Our findings indicate a consistent vegetation decline at a rate of 0.051 ± 0.043/year, driven by rising temperatures, and declining rainfall, which is exacerbated by anthropogenic land use pressure since 2000. Human population growth is strongly correlated with cropland expansion (R2 = 0.903) and vegetation loss (R2 = 0.793). As a result, 53.85% of species populations are declining, with 30.77% classified as endangered or vulnerable. Based on the scientific evidence, NbSs have emerged as cost-effective and sustainable strategies to restore ecological function and strengthen communities-based conservation. The proposed NbS framework offers a holistic pathway for safeguarding long-term ecosystem resilience in dryland reserves, directly contributing to Sustainable Development Goals (SDGs) 13 and 15.